Socialization of Simple Financial Report Bookkeeping Methods for MSME Actors in Laundry Service Businesses in Caturtunggal Village - Annisa, Annisa; Astuti, Tutut Dewi (PT FORMOSA CENDEKIA GLOBAL, 2024)
Two business actors (MSME) located in Caturtunggal sub-district, Depok District, Sleman Regency participated in this community service to improve MSMEs understanding of simple financial report bookkeeping. The techniques used were surveys, interviews, and socialization. Choosing these two business actors because of their lack of understanding of simple financial report bookkeeping. This activity was carried out in stages by visiting business actors one by one at their workplaces. The results showed that business actors gained a better understanding of simple financial report bookkeeping.